If Channel Inhibition With Ivabradine Does Not Improve Cardiac and Vascular Function in Experimental Septic Shock. Issue 3 (September 2016) - Wei, Chaojie; Al Kattani, Narimane; Louis, Huguette; Albuisson, Eliane; Levy, Bruno; Kimmoun, Antoine
ABSTRACT: Objective: Previous studies have suggested that lowering heart rate (HR) by selective β1-blockers improves sepsis-induced cardiac and vascular dysfunction primarily by decreasing proinflammatory pathways. However, the impact of isolated heart rate reduction (HRR) on hemodynamics and inflammatory pathways remains unknown. The present study was designed to assess the effects of HRR by ivabradine, an I f channel inhibitor, on cardiovascular function and inflammatory pathways in peritonitis-induced septic shock in rats. Design: Randomized animal study. Setting: University research laboratory. Interventions: Four hours after cecal ligation and puncture (CLP), Wistar rats were randomly allocated to the following groups: CLP (n = 8) and CLP + ivabradine (n = 8, administered per os 4 h after the surgery). Another eight Wistar male rats underwent sham operation. All rats received a continuous infusion of saline (10 mL kg −1 h −1 ), analgesic (nalbuphine: 0.2 mg kg −1 h −1 ), and antibiotics (imipenem and cilastatin sodium: 10 mg kg −1 ) 4 h after the surgery. Assessment at 18 h included hemodynamics, in vivo cardiac function by echocardiography, and ex vivo vasoreactivity by myography. Circulating cytokine levels (TNF-α, IL-6, and IL-10) were measured by ELISA, whereas cardiac and vascular protein expressions of NF-κB/IκBα/iNOS and Akt/eNOS were assessed by Western blotting. Results: Compared with sham animals, CLP induced tachycardia, hypotension, decreased cardiac output, hyperlactatemia, and vascular hyporesponsiveness to vasopressors. Compared with the CLP group, adjunction of ivabradine decreased the HR without any impact on blood pressure, lactatemia, or vascular responsiveness to vasopressors. Adjunction of ivabradine to CLP rats had no impact on TNF-α, IL-6, and IL-10 cytokines, or on the protein expression levels of phosphorylated forms of NF-κB, Akt, eNOS, and degradation of IκBα in cardiac and vascular tissues. Conclusion: Isolated HRR by ivabradine in an experimental model of septic shock does not appear to be associated with any effect on the tested parameters of cardiac function or on vascular responsiveness to vasopressors. Moreover, in this setting, ivabradine does not alter the circulating levels of selected pro/anti-inflammatory cytokines or cardiac and vascular NF-κB/IκBα protein expression levels. Abstract : Supplemental Digital Content is available in the text